Powassan Encephalitis: A Case Report from New York, USA - Danielle A. Bazer; Matthew Orwitz; Nicholas Koroneos; Olga Syritsyna; Elizabeth Wirkowski (Case Reports in Neurological Medicine)
Background. Powassan is a positive-sense, single-stranded, enveloped RNA virus that is a tick-borne Flavivirus, transmitted by Ixodes species, with groundhogs being the usual mammalian host. The virus is endemic to North America, with peak transmission during the summer and fall. The incubation period is 7–34 days, followed by a prodrome of flu-like symptoms. Although most infected individuals are asymptomatic, the virus can penetrate the CNS to produce a viral encephalitis. The key to the diagnosis is a positive serology. Results. The patient is a 62-year-old male with a past history of a right putamen infarct, hepatitis C, hypertension, and substance abuse who presented due to acute onset altered mental status, dysarthria, and left-sided facial droop. He had several tick bites around the time of presentation in December. He was empirically treated for possible meningitis, as CSF revealed WBC 370 (80% mononuclear cells); RBC 10, protein 152 mg/dL, and glucose 59 mg/dL. An MRI scan of the brain showed a subacute left putamen stroke. MRAs of the head and neck were unremarkable. A Mayo Clinic Encephalopathy Panel was unremarkable; however, a New York State Arbovirus panel revealed Powassan IgM ELISA as well as Powassan Polyvalent microsphere immunofluorescence assay reactivity. His hospital course was complicated by critical illness myopathy and respiratory failure requiring tracheostomy. Conclusion. The Powassan virus is a known etiology for encephalitis in North America. Although the peak incidence of transmission is in the summer and fall, this does not exclude transmission during other seasons. Due to the increasing prevalence of Powassan virus in Lyme-endemic areas particularly in the Midwest and Northeast, United States, patients with an unexplained altered mental status in these regions should be screened for Powassan virus, regardless of the time of year.